Academic writing : a handbook for international students - Bailey, Stephen, 1947- (Routledge, 2018)
Clearly organised into four parts, this new edition allows teachers and students to quickly find help they need with all writing tasks. Each part is divided into short sections containing explanations, diagrams and practice exercises, for use in the classroom or for self-study.